2015
DOI: 10.1186/s13071-015-1020-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of advantus™(imidacloprid) soft chewable tablets for the treatment of Ctenocephalides felis infestations on dogs

Abstract: BackgroundStudies reported here were conducted to evaluate the safety and effectiveness of advantus™ (imidacloprid) soft chewable tablets for the treatment of flea (Ctenocephalides felis) infestations on dogs and puppies 10 weeks of age or older and weighing 4 pounds or greater.MethodsA pharmacokinetic study was conducted to evaluate parameters of orally administered imidacloprid. A dose confirmation study was conducted to confirm the efficacy of 0.75 mg/kg at 8, 12 or 24 hours post-treatment. A knockdown and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…A soft chewable tablet containing imidacloprid given to puppies and adult dogs provided 96% kill of fleas at 4 h [ 368 ].…”
Section: Pest Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A soft chewable tablet containing imidacloprid given to puppies and adult dogs provided 96% kill of fleas at 4 h [ 368 ].…”
Section: Pest Managementmentioning
confidence: 99%
“…Within 2 weeks, 81–88% of the dogs were flea free. In a pharmacokinetic study, a soft chewable tablet containing imidacloprid given daily for 14 days provided 98% kill of adult fleas [ 368 ].…”
Section: Pest Managementmentioning
confidence: 99%
“…The only study published about this commercial product used dogs from different clinics and different breeds. At the oral dose of 0.75 mg/kg BW, the study reported no adverse effect in the 118 dogs treated, and 95% efficacy at controlling fleas infestations . Studies of rodents fed on diets with imidacloprid concentrations of 250 mg/kg reported sand fly mortality after blood fed on treated rodents > 85% for at least 3 days post‐treatment .…”
Section: Resultsmentioning
confidence: 99%
“…Імідоклоприд використовується у багатьох галузях та комбінаціях як інсектицидна діюча речовина, що й обумовлює ефективність застосування при блошиній інвазії (Huang & Lien, 2013;Qureshi et al, 2015).…”
Section: таблицяunclassified